"Financial Services Modernization:" A Cure for Problem Banks? - Kirk K. Van Tine; Robert G. Boggess II (Washington University Law Quarterly, 1991)
On February 5, 1991, after consulting federal financial regulatory agencies and other interested governmental parties, the Department of the Treasury transmitted to Congress its report: Modernizing the Financial System: Recommendations for Safer, More Competitive Banks." The Treasury Report concludes that four major problems confront the U.S. banking system: (1) reduced bank competitiveness and financial strength, caused by outdated legal restrictions that prevent banks from responding to changing financial markets and technology; (2) the overextension of deposit insurance, resulting in excessive exposure for taxpayers and weakened market discipline for banks; (3) a fragmented regulatory system that has created duplicative rules and has often failed to produce decisive remedial action; and (4) an undercapitalized deposit insurance fund. To address these problems, the Treasury Report recommends four fundamental legislative reforms: (1) to increase bank competitiveness, Congress should authorize nation-wide banking, new financial activities for banks, and commercial ownership of banks; (2) to reduce taxpayer exposure and increase market discipline, Congress should reduce the scope of deposit insurance, require a link between regulatory supervision and capital strength, and require risk-based insurance premiums for deposit insurance; (3) to reduce duplicative rules and produce decisive remedial action, Congress should streamline the federal regulatory system; and (4) to recapitalize the Bank Insurance Fund, Congress should adopt a funding plan based on contributions from the banking industry, rather than from the Treasury and the taxpayers. After a very basic historical review of past attempts to "reform" the banking industry, this Article focuses on the less publicized portions of the Treasury recommendations in an attempt to identify some of the issues that would remain unsettled, even if the proposals are enacted into law.
Keywords: Financial services industry